Project on nuclear issues : a collection of papers from the 2015 conference series - Anderson, Justin (Center for Strategic and International Studies ; Rowman & Littlefield, 2016)
This annual volume includes papers from the 2015 CSIS Project on Nuclear Issues' Capstone Conference.